2009
DOI: 10.1007/s11010-009-0250-y
|View full text |Cite
|
Sign up to set email alerts
|

Advanced glycation endproducts alter functions and promote apoptosis in endothelial progenitor cells through receptor for advanced glycation endproducts mediate overpression of cell oxidant stress

Abstract: Endothelial progenitor cells (EPCs) play an important role in preventing atherosclerosis. The factors that regulate the function of EPCs are not completely clear. Increased formation of advanced glycation endproducts (AGEs) is generally regarded as one of the main mechanisms responsible for vascular damage in patients with diabetes and atherosclerosis. AGEs lead to the generation of reactive oxygen species (ROS) and part of the regenerative capacity of EPCs seems to be due to their low baseline ROS levels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 27 publications
7
54
0
2
Order By: Relevance
“…Predominantly, changes in ROS and hypoxia from neighboring cells in the presence of excessive glucose alter juxtacrine and paracrine signaling to the stem cells. 77,78 Moreover, diabetes causes an influx of inflammatory cells and stimulates adipocyte production, altering the stem cell microenvironment. 79 These molecular changes are addressed in this section.…”
Section: Molecular Pathways That Underlie Stem Cell Dysfunction Durinmentioning
confidence: 99%
“…Predominantly, changes in ROS and hypoxia from neighboring cells in the presence of excessive glucose alter juxtacrine and paracrine signaling to the stem cells. 77,78 Moreover, diabetes causes an influx of inflammatory cells and stimulates adipocyte production, altering the stem cell microenvironment. 79 These molecular changes are addressed in this section.…”
Section: Molecular Pathways That Underlie Stem Cell Dysfunction Durinmentioning
confidence: 99%
“…In line, Wu et al identified HO-1 as a potent stimulus for increasing circulating EPC numbers; however the underlining mechanisms remain unclear (129). An increase in advanced glycylation endproducts (AGEs) or oxidized LDLs can impair endothelial and EPC function by increasing ROS levels (15,101,102). However, this effect could be blocked by siRNA against the receptor for advanced glycation endproducts (RAGE) or blockade of the oxLDL receptor LOX-1 (94,101).…”
Section: Importance Of Oxidative Stress To Epc Functionmentioning
confidence: 99%
“…However, this effect could be blocked by siRNA against the receptor for advanced glycation endproducts (RAGE) or blockade of the oxLDL receptor LOX-1 (94,101). RAGE is also regulated by C-reactive protein (CRP), which is considered as a proatherosclerotic protein, resulting in impaired EPC function (15). Accordingly, AGE treatment leads to a downregulation of eNOS and Bcl-2 expression, as well as an elevation in cyclooxygenase-2, Bax, NF-kappaB, and caspase-3 in a MAPK (ERK=P38=JNK)-dependant manner (83).…”
Section: Importance Of Oxidative Stress To Epc Functionmentioning
confidence: 99%
“…Glucose also upregulates the expression of the receptor for advanced glycation end products (RAGE) and the RAGE pathway is known to promote apoptosis. 29,30 Like glucose transporters, RAGE expression was comparable in control and NF-kB p65 knockout thymocytes (Supplementary Figure 4). Thus, it appears that it is a lack of survival factors in the knockout cells that lead to their apoptosis and not a lack of glucose transporters or RAGE.…”
mentioning
confidence: 94%